2020
DOI: 10.5505/kpd.2020.54765
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of childhood traumas in inpatient adults with major depression and with or without attention deficit hyperactivity disorder comorbidity (eng)

Abstract: Investigation of childhood traumas in inpatient adults with major depression and with or without attention deficit hyperactivity disorder comorbidity Yatarak tedavi gören major depresyon ve dikkat eksikliği hiperaktivite bozukluğu eş tanısı olan ve olmayan erişkinlerde çocukluk çağı travmalarının incelenmesi SUMMARY Objective: Attention deficit hyperactivity disorder (ADHD) is one of the most common neurodevelopmental disorders of childhood and a significant number of symptoms continue in adulthood. Depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Yet another meta-analysis study found that the probability of depression increased when they calculated the long-term outcomes of childhood trauma (Humphreys et al, 2020). Erdoğan et al (2020) suggested that childhood traumas may be taken into evaluation in individuals with depression and concomitant attentiondeficit/hyperactivity disorder. Childhood traumas may be the underlying cause in patients with affective, anxiety, and somatoform disorders (Carlier et al, 2016).…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet another meta-analysis study found that the probability of depression increased when they calculated the long-term outcomes of childhood trauma (Humphreys et al, 2020). Erdoğan et al (2020) suggested that childhood traumas may be taken into evaluation in individuals with depression and concomitant attentiondeficit/hyperactivity disorder. Childhood traumas may be the underlying cause in patients with affective, anxiety, and somatoform disorders (Carlier et al, 2016).…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%
“…It is known that the childhood traumas influence an individual in older ages in the form of psychological problems such as decreased self-esteem and socialization, impairment in interpersonal functioning, withdrawal, and self-harm (Gören & Tıraşçı, 2007;Kahveci, 2016) and observation of behavioural aspects such as decrease in executive functions and increase in impulsivity (Shin et al, 1999;Türksoy, 2003). Along with these effects, the research support that the childhood traumas cause several psychopathologies such as personality disorder, dissociative disorders (Bennet, 2016;Fung et al 2019), substance addiction, somatoform disorder, anxiety disorder and depression (Bifulco, Brown, & Adler, 1991;Erdoğan, Delibaş, & Baskin, 2020;Humphreys et al, 2020;Lindert et al, 2014;Olafson, 2014;Özen, Antar, & Özkan, 2007;Stein et al. 1996;Haj-Yahia & Tamish, 2001;Vallati et al, 2020).…”
Section: Introductionmentioning
confidence: 96%